The Methodology of evolutionary and neoclassical economics as a consequence of the changes in the concept of human nature - Horodecka, Anna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The concept of human nature builds the basis for thinking about economics and its fundamental elements such as methodology, methods and crucial theories. Therefore, changes in the concept of human nature lead to changes in the fundamentals of economics. The goal of the paper is to present this impact using the example of evolutionary and neoclassical economics. The method applied to this research is, among others, a content analysis of the selected texts developed within neoclassical and evolutionary economics and the research undertaken about them. The analysis proves that the main differences between these economic schools might be explained by the diverse assumptions about human nature
Argumenta Oeconomica, 2017, Nr 1 (38), s. 129-166
Keywords: methodology of economics; concept of human nature; neoclassical economics; evolutionary economics